Design of Microhydro Power Plants Based on Load Flow and Short Circuit Study Using ETAP: A Case Study in East Java, Indonesia - Chico Hermanu Brillianto Apribowo; Muhammad Nizam; Agus Ramelan; Hari Maghfiroh; Aulia Vici Yunitasari (Universitas Sebelas Maret (UNS), 2022)
This study was conducted to determine the feasibility level of the microhydro power plant development plan in Ngentep Village for the Off Grid On Grid system system and Sarangan Lake, Magetan Regency, East Java. The methodology used includes field survey activities, hydrological analysis, power and energy calculations, mechanical and electrical equipment planning, and technical analysis. In this system there are 4 study cases, including the Off Grid system in Ngntep, the Off Grid system with Hybrid in Ngentep, the On Grid system in Sarangan Lake and the on grid system with hybrid in Sarangan Lake. The results showed that the water discharge was able to generate minimal power in Sarangan Lake and Ngentep, 1.59kW and 1.18kW respectively. Power value for the On Grid system with a value of 1,598 kW. While the power value for Off Grid is 0.072 kW. And has a power factor of up to 99.7% but this is very helpful for the community, especially those in remote rural areas and suppliers in tourist areas. As for the current value in the On Grid system is 2.126 kA and for the Off Grid system it is 1.0209 kA.